Method of Drilling Process Control and Experimental Studies of Resistance Forces During PDC Cutter Drilling - Solixov J. X.; Barotov V. N.; Ravshanov Z. Y.; Ergasheva Z. A. (Scientific Trends, 2025)
An effective control system, grounded in theoretical principles and empirical validation, is essential for optimizing the drilling process while minimizing time and material costs. The advent of advanced rock-cutting tools, particularly polycrystalline diamond (PDC) cutters, has highlighted the need for developing methods and criteria for optimal drilling process control, especially for applications involving medium-hard rocks. This paper analyzes the forces at play between the rock-cutting elements, the rock face, and the drilling mud, identifying key influencing factors and providing formulas to determine rock failure parameters. Empirical validation of the theoretical concepts was conducted using data from experimental drilling of marble with 76.2 mm diameter PDC cutters. The experiments employed a full factorial design to develop mathematical models and graphical representations of the influencing factors. The method proposed for controlling the drilling process focuses on finding the optimal balance between tool rotation frequency, axial weight, and penetration per rotation. This approach enables the identification of the rock failure mode at the bottom of the well through indirect indicators, facilitating the selection of drilling parameters that maximize mechanical drilling speed while ensuring efficient operation of the rock-cutting tool. A schematic is included, outlining potential bit operation modes and methods for recognizing them based on the ratios of penetration per rotation and the rotation frequency of the cutting tool.
Keywords: Diamond drilling; full factorial experiment; drilling process control; drilling tool development; PDC cutters; drilling modes.